ChemInform Abstract: Dioxirane‐Mediated Metal‐Free Oxidations of Target Molecules Containing Unsaturated Carbons. Issue 29 (July 2015) - D'Accolti, Lucia; Annese, Cosimo; Fusco, Caterina
Abstract Review: 141 refs.